FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM DI WILAYAH KERJA PUSKESMAS PANTOLOAN KECAMATAN TAWAELI KOTA PALU TAHUN 2015 - Rizqy Wahyuni; Nuraiman Nuraiman; Elfina Elfina (Universitas Pahlawan, 2022)
This study aims to determine the relationship between age and knowledge with low IUD use in the Pantoloan Health Center, Tawaeli District,. The research design used an analytical survey with a Cross Sectional Study approach. The population is all active family planning acceptors in the Pantoloan . The sample is 43 people using the Slovin formula, the sample is selected using the simple random sampling method where the sample is taken by drawing a sample. Collecting data through interviews using a questionnaire. Data analysis was in the form of univariate and bivariate analysis using the Chi-Square Statistical Test = 0.05 and presented in the form of a frequency distribution table and analysis. The results of the bivariate analysis showed that there was no relationship between age and low IUD use in the Pantoloan Public Health Center, Tawaeli District, Palu (p.value = 0.376>0.05), and there is a relationship between knowledge and the low use of IUDs in the Pantoloan Health Center Work Area, Tawaeli District, Palu (p.value = 0.027 <0.05). Conclusions in this study There is no relationship with the low use of IUDs in the Pantoloan Health Center Work Area, Tawaeli District, Palu and there is a relationship between knowledge in the Pantoloan Health Center Work Area, Tawaeli District Kota Palu. Keywords : IUD, Age and Knowledge.